Human cytomegalovirus glycoprotein complex gH/gL/gO uses PDGFR-α as a key for entry - Wu, Yiquan; Prager, Adrian; Boos, Simone; Resch, Moritz; Brizic, Ilija; Mach, Michael; Wildner, Sabrina; Scrivano, Laura; Adler, Barbara (PLoS Pathogens, 2017)
Herpesvirus gH/gL envelope glycoprotein complexes are key players in virus entry as ligands for host cell receptors and by promoting fusion of viral envelopes with cellular membranes. Human cytomegalovirus (HCMV) has two alternative gH/gL complexes, gH/gL/gO and gH/gL/UL128,130,131A which both shape the HCMV tropism. By studying binding of HCMV particles to fibroblasts, we could for the first time show that virion gH/gL/gO binds to platelet-derived growth factor-α (PDGFR-α) on the surface of fibroblasts and that gH/gL/gO either directly or indirectly recruits gB to this complex. PDGFR-α functions as an entry receptor for HCMV expressing gH/gL/gO, but not for HCMV mutants lacking the gH/gL/gO complex. PDGFR-α-dependent entry is not dependent on activation of PDGFR-α. We could also show that the gH/gL/gO-PDGFR-α interaction starts the predominant entry pathway for infection of fibroblasts with free virus. Cell-associated virus spread is either driven by gH/gL/gO interacting with PDGFR-α or by the gH/gL/UL128,130,131A complex. PDGFR-α-positive cells may thus be preferred first target cells for infections with free virus which might have implications for the design of future HCMV vaccines or anti-HCMV drugs.
EVALuna2:33768